Sirri Marriage Celebration and Its Impact on Social Change in Banjarese Community, South Kalimantan - Anwar Hafidzi; Bahran Bahran; Fuad Luthfi; Rusdiyah Rusdiyah; Mohd. Hatta Mohamed Ali; Ali Banaeian Esfahani (Al-Ahkam, 2022)
This study seeks to reveal that sirri marriages, which are usually secret, in the Banjar community are carried out openly and are carried out by walimah 'ursy (wedding ceremonies). In contrast to other studies, most of them only discuss the law of unregistered marriage and its legality in Indonesia. This study tends to pay more attention to aspects of habits and shifts in the meaning of the sirri marriage. The method used in this study is empirical with an ethnographic-phenomenological approach to the celebration of sirri marriages in the Banjar community, South Kalimantan. The results of this study prove that the legality of sirri marriages is illegal in Indonesia State because it is not recorded at the Office of Religious Affairs. However, aspects of the habit of unregistered marriages and holding wedding celebrations in the Banjar community,  make sirri marriages "as if" they have legal rights in society based on social norms.